KUALITAS EKSTERNAL TELUR PADA PUYUH (Cortunix Cortunix Japonica) YANG DIBERI RANSUM KOMERSIL MENGANDUNG TEPUNG KENCUR - Najian, Irfan; Sudrajat, Deden; Jatmiko (Jurnal Peternakan Nusantara, 2021)
Quail are livestock that are kept for their eggs and meat. Raising quail is more economical than other types of poultry. Kencur contains starch, minerals and essential oils which are expected to have an influence on the external quality of quail eggs. The purpose of this study was to examine the effect of commercial feed mixed with kencur flour on the external quality of quail eggs (Cortunix cortunix japonica). This research was conducted on 22 March – 18 May 2020. The livestock used in this study were 64 quails aged 7 days and data collection began when the quails were 44 days – 65 days old. This research used Completely Randomized Randomized (CRD) consisting of 4 treatments and 4 replications, each treatment consisted of 4 quails. The treatments were P1 = Control feed without any addition, P2 = Addition of 0.5% kencur flour, P3 = Addition of 1% kencur flour, P4 = Addition of 1.5% kencur flour. The variables measured were egg weight, egg index, shell weight and shell thickness. The results of this study showed that the addition of kencur flour in quail did not affect the external quality of quail eggs. Key words: External Quality, Quail, Kencur,